A Base on Fuzzy Theory to Supplier Evaluation and Selection Optimization. (5th October 2020) - Lin, Chun-Tsai
Abstract : Supplier evaluation and selection is critical for schools to save costs. Supplier evaluation indexes must be developed before evaluation. In addition, how to select the most appropriate supplier and make the best procurement decision are also important topics. This study selected three most important supplier evaluation and selection criteria and established a supplier evaluation model through fuzzy logic inference using MATLAΒ. This method can overcome the defects in some methodologies and improve organizational capability and competitiveness. This model can also be used to address practical supplier evaluation and selection matters. Modelling took several steps, including fuzzification, fuzzy rule base, fuzzy inference engine, and defuzzification. Then, a supplier evaluation model was established based on the fuzzy rules obtained from the abovementioned operations. This model can provide a basis for school purchasers or managers in executing supplier selection policies in the future.